DIGITALISASI DAN PENGANGGURAN DI PEDESAAN JAWA TIMUR PADA MASA PANDEMI COVID-19 (STUDI KASUS PADA SEKTOR INFORMAL) - Mawarni, Sherina Indah; Syafitri, Wildan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
The COVID-19 pandemic has caused unemployment increase, but COVID-19 has also provided a digital acceleration boost. In 2020 East Java has highest rate of digital literacy. Using SAKERNAS 2020 data, This study employs logistic regression to determine how East Java's unemployment is affected by digitalization. This study indicated that East Java's unemployment rate was significantly and negatively impacted by digitization. Workers who can master information technology through use of the internet will have an impact on have a smaller tendency to become unemployed than those who cannot use the internet. In addition, other factors such as area of residence, employment sector, gender, training, pre-employment card ownership, education and migration also affect the tendency of the workforce to become unemployed.